Impact of catechol-O-methyltransferase gene variants on methylation status of P16 and MGMT genes and their downregulation in colorectal cancer. Issue 2 (March 2019) - Wani, Hilal A.; Majid, Sabhiya; Bhat, Arif A.; Amin, Shajrul; Farooq, Rabia; Bhat, Showkat A.; Naikoo, Nissar A.; Beigh, Mushtaq A.; Kadla, Showkat A.
Abstract : Globally, colorectal cancer (CRC) is the third most commonly diagnosed cancer in males and the second most commonly diagnosed cancer in females, with 1.4 million new cases and almost 694 000 deaths estimated to have occurred in 2012. The development and progression of CRC is dictated by a series of alterations in diverse genes mostly proto-oncogenes and tumor suppressor genes. In this dreadful disease disturbances different from mutations called as epigenetic regulations are also taken into consideration and are thoroughly investigated. The present study was designed to analyze the promoter hypermethylation of CpG (cytosine, followed by guanine nucleotide) islands of cyclin-dependent kinase inhibitor 2A ( P16 ) and O 6 -methylguanine-DNA methyltransferase ( MGMT ) genes and its subsequent effect on the protein expression in CRC. The impact of the common functional polymorphism of the catechol- O -methyltransferase ( COMT ) gene, Val158Met, on promoter hypermethylation of P16 and MGMT genes in CRC was also investigated. The study included 200 CRC cases and equal numbers of normal samples. DNA was extracted using the kit method and methylation specific-PCR was performed for analysis of the promoter hypermethylation status. Total protein was isolated form all CRC cases and western blotting was performed for P16 and MGMT proteins. The COMT Val158Met polymorphism was analyzed by a PCR-restriction fragment length polymorphism assay. Epigenetic analysis showed that unlike other high-risk regions, the Kashmiri population has a different promoter hypermethylation profile of both P16 and MGMT genes, with frequent and significant promoter hypermethylation of both in CRC. The frequency of promoter hypermethylation of both genes was significantly higher in males and was insignificantly found to be higher in stage III/IV. The degree of P16 and MGMT promoter hypermethylation increased significantly with increasing severity of the lesion. We also found a significant correlation between P16 and MGMT promoter hypermethylation and loss of protein expression in CRC. A significant association was found between COMT polymorphism (homozygous variant) and P16 methylation status. Similar results were also found for MGMT hypermethylated cases.